How Should We Classify Kawasaki Disease? - Marrani, Edoardo; Burns, Jane C.; Cimaz, Rolando (Frontiers in Immunology, 2018)
The exact classification of Kawasaki disease (KD) has been debated. Infectious disease specialists have claimed it as an infection with a classic immune responses to an as yet unidentified pathogen that localizes to the coronary arteries. Others have favoured an autoreactive hypothesis that KD is triggered by an antigen that shares homology with structures in the vascular wall, and the molecular mimicry resulting in an immune response directed to that tissue. Rheumatologists have classified it as a systemic vasculitis, while some immunologists have stressed the robust nature of the innate immune response that causes both systemic inflammation as well as damage to the coronary arterial wall and questioned whether KD falls within the spectrum of autoinflammatory diseases. This review will describe the evidences avaulable up to now regarding these hypotheses.